Examination of Self-directed Learning Readiness Level of Students During the COVID-19 Pandemic - Firda Mufidah, Elia; Asli Pravesti, Cindy; Lia Prayitno, Lydia; Wahyuni, Fitri; Mutianingsih, Ninik (KnE Social Sciences, 2022)
The changes in learning patterns during the COVID-19 pandemic demanded students to take initiative, persevere, and learn independently. Thus, this study examines the level of students’ self-directed learning readiness. The research design used was quantitative with a descriptive method. A total of 285 participants – 46 male and 239 female – were included in the study sample. The measuring instrument used was a self-directed learning readiness scale. Data analysis was done using an independent sample t-test and the assumptions were tested first, obtaining an average value of 56.16 and a standard deviation of 5.71. The results indicated that H0 was accepted, which implies that there is no significant difference in the average self-directed learning readiness between male and female students with a t value < t Table (